Direct Synthesis of MOF-74 Materials on Carbon Fiber Electrodes for Structural Supercapacitors - David Martinez-Diaz; Pedro Leo; David Martín Crespo; María Sánchez; Alejandro Ureña (Nanomaterials, 2024)
The use of fossil fuels has contributed significantly to environmental pollution and climate change. For this reason, the development of alternative energy storage devices is key to solving some of these problems. The development of lightweight structures can significantly reduce the devices’ weight, thereby reducing energy consumption and emissions. Combining lightweight structures with alternative energy storage technologies can further improve efficiency and performance, leading to a cleaner and more sustainable system. In this work, for the first time, MOF-74 materials with different divalent metal ions have been synthesized directly on carbon fiber, one of the most widely used materials for the preparation of electrodes for supercapacitors with structural properties. Different techniques, such as nitrogen adsorption–desorption isotherms, cyclic voltammetry or galvanostatic charge–discharge, among others, were used to evaluate the influence of the metal cation on the electrochemical capacitance behavior of the modified electrodes. The Co-MOF-74 material was selected as the best modification of the carbon fibers for their use as electrodes for the fabrication of structural supercapacitors. The good electrochemical performance shown after the incorporation of MOF materials on carbon fibers provides a viable method for the development of carbon fiber electrodes, opening a great variety of alternatives.